The Effect of Using the Sharing Application (Tik-Tok) on the Character Development of Elementary School Children - Fatmawati Nur Hasanah; Kristiyah Kristiyah (Attadrib: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2023)
The development of information technology has changed people's lives in all civilizations and cultures. One of the various and most favorite social media for elementary school children today is the sharing application "Tik-Tok". The use of the "Tik-Tok" application is felt as a means to prevent children from getting bored in between activities. Apart from eliminating boredom, the "Tik-Tok" application also has a big impact on children's character development. This study aims to determine the level of use of the Tik-Tok sharing application in elementary school-age children, to determine the level of character development of elementary-age children, and to determine the impact of using the Tik-Tok sharing application on the character development of elementary school-age children in Klidang Wetan Village, District Batang, Batang Regency. This research approach through a quantitative approach to the type of field research. This research data collection techniques through observation methods, survey methods and documentation methods. The number of samples consisted of 115 students in grades IV, V and VI of SDN Klidang Wetan, Batang District, from a total population of 161. The results showed that the use of the Tik-Tok Sharing Application in Klidang Wetan Village, Batang District, was included in the high criteria. Meanwhile, the level of character development of elementary school children in Klidang Wetan Village is included in the high criteria. In addition, the effect of using the Tik-Tok Sharing Application affects character development. The coefficient (R) obtained from the statistical test is 0.386 and the coefficient of determination R-square is 0.149. In short, the transformative effect of using the Tik-Tok Sharing Application on the character development of Elementary School-aged children is 14.9%, the remaining 85.1% is the influence of other factors.